2012
DOI: 10.5402/2012/103817
|View full text |Cite
|
Sign up to set email alerts
|

Substitution Effects of C-C Triple Bonds on Deactivation Processes from the Fluorescent State of Pyrene Studied by Emission and Transient Absorption Measurements

Abstract: Pyrenes substituted with tert-butylethynyl, trimethylsilylethynyl, and trimethylsilylbutadiynyl groups were prepared, and the fluorescence yields (Φ f ), lifetimes, and triplet-triplet absorption were measured in cyclohexane. Upon introduction of the groups possessing triple bond(s) to the pyrene skeleton, the fluorescence rate (k f ) increased. The variation of the terminating groups did not appreciably affect the Φ f and k f values. Increasing the number of the triple bond, the k f values increased by the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However both triplet and fluorescence yields increased. It has been reported that the presence of triple bonds enhances the intersystem crossing rate in addition to enhancing fluorescence as stated above [34]. Thus the presence of triple bonds enhances both fluorescence and triplet yields.…”
Section: Triplet Quantum Yields and Lifetimesmentioning
confidence: 89%
See 1 more Smart Citation
“…However both triplet and fluorescence yields increased. It has been reported that the presence of triple bonds enhances the intersystem crossing rate in addition to enhancing fluorescence as stated above [34]. Thus the presence of triple bonds enhances both fluorescence and triplet yields.…”
Section: Triplet Quantum Yields and Lifetimesmentioning
confidence: 89%
“…It has been reported that the introduction of groups containing triple bonds increases fluorescence rate [34]. It should also be noted that complexes 1, 2 and 3 are asymmetrical with only one substituent; this implies that any structural change to the Pcs at that point of substitution would also impact on the properties of the newly formed complexes.…”
Section: Photophysical Propertiesmentioning
confidence: 98%
“…As a result of a reduction in symmetry, the forbidden S 0 / S 1 transition of chrysene becomes allowed, which is reected by an increase in the absorption coefficient (3). 65 The emission maximum of 3 is red-shied by 23 nm compared to chrysene (1). Furthermore, the uorescence quantum yield (F F ) increases from 0.14 for chrysene to 0.41 for the dialkynyl derivative 3 ( Table 2), also as a result of the aforementioned symmetry decrease.…”
Section: Uv-vis Absorption and Uorescence Spectramentioning
confidence: 99%
“…Organic substances have some advantages in applications to photoactive materials because they possess unique luminescence properties that are governed by precise molecular designs [1][2][3][4][5][6]. Previously, we and others observed that linking silyl and silylethynyl groups to fused aromatic substances such as naphthalene [7][8][9], anthracene [7,10,11], pyrene [7,[12][13][14][15][16][17] and perylene [18] often increases fluorescence efficiency. However, the highly emissive character of these molecules is limited to highly dilute solutions because fluorescence intensities generally decrease as the concentrations of solutions increase.…”
Section: Introductionmentioning
confidence: 99%